Strategi Guru Akidah Akhlak dalam Membentuk Karakter Peserta Didik di MTs Ma'arif 02 Kota Gajah Lampung Tengah - M.Mahrus; Irhamudin; Adi Wijaya (CV. Creative Tugu Pena, 2024)
Teachers are professional educators who have the main task of educating, guiding, teaching, directing, training, assessing, and providing evaluations to students in early childhood education. Learning strategies are a series of activities in which these activities use methods and utilization of resources that have been arranged so that the planned learning objectives can be realized. This study is about the Strategy of Aqidah Akhlak Teachers in Forming the Character of Students at MTs Ma'arif 02 Kota Gajah, Central Lampung. The purpose of this study is to determine the Strategy of Aqidah Akhlak Teachers in Forming the Character of Students at MTs Ma'arif 02 Kota Gajah, Central Lampung. This study is a study that uses a descriptive approach with a type of qualitative field research. The sources of this study are aqidah akhlak teachers, principals of madrasahs, and class 8 students of MTs Ma'arif 02 Kota Gajah. The data collection methods used are interview techniques, observation and documentation. Data analysis was carried out by collecting data, conducting analysis and drawing conclusions. The results of the study showed that the Akidah Akhlak Teacher's Strategy in Forming Student Characters included teachers forming self-awareness in students about the importance of having character, teachers getting students used to independent learning, teachers providing motivation and direction to students to compete healthily and have self-confidence, teachers providing examples and examples of these characters both in and outside the classroom. In the learning process, the Akidah Akhlak Teacher uses expository learning strategies, affective learning strategies and cooperative learning strategies. The purpose of these three strategies is for students to have good character or noble morals.